The Relationship Between Social Support And Resilience In Final Semester Student With Self-Efficacy Mediation - Lazuardi Ikhwan (PT. Hasba Edukasi Mandiri, 2025)
Final year students will work on their final assignment in the form of a scientific work, namely a thesis, so that final semester students are required to take the thesis course because it is used as a prerequisite for students to obtain a bachelor's degree. Generally, final year students are given time to work on their thesis within one semester or within six months. However, in reality, many students need more than six months to work on it . Based on the results of data collection that has been carried out, it shows that there is no happen connection direct between Social Support and Resilience will but through the mediation of Self-Efficacy. This shows that social support through the mediation of self-efficacy will produce higher resilience compared to the relationship between social support and resilience without the mediation of self-efficacy. This shows that the mediation variable plays a role in increasing resilience. This means that the higher the social support given and the high self-efficacy of the individual, the higher/stronger a person's resilience will be, the lower the social support and self-efficacy of the individual, the resilience will also decrease.